Проблема трипільського спадку в Україні і питання індоєвропейської прабатьківщини - Балушок, В. (Народна творчість та етнографія, 2005)
The search of Ukrainians for their ethnical and historical origins made the discussions around Trypillya archeological culture and its connection to Ukrainians more actual and active. There a lot of attitudes toward the Trypillya culture and they go to two different extremes: from direct identification of the Ukrainians with the creators of the Tryp³llyà culture to complete deny of the Tryp³llyà heritage as possible ancestors of Ukrainian Ethnos. The author of this article is making an attempt to look at this topic and give his hypothesis of the Tryp³llyà heritage in the contemporary Ukraine, the destiny of "Tryp³llians" and the question of the existence of common Indo-European Pre-Motherland from the ethnological point of view. Ethno-genetic approach, which is using in his analyses the author of this article makes one to analyze this topic as a complex, including the materials collected by archeologists, linguists, anthropologists, folkloristic, geography.